Case Report: Arterial Wall Inflammation in Atherosclerotic Cardiovascular Disease is Reduced by Olamkicept (sgp130Fc) - Schulte, Dominik M.; Waetzig, Georg H.; Schuett, Harald; Marx, Marlies; Schulte, Berenice; Garbers, Christoph; Lokau, Juliane; Vlacil, Ann-Kathrin; Schulz, Juliane; Seoudy, Anna K.; Schieffer, Bernhard; Rosenstiel, Philip; et al. (Frontiers in Pharmacology, 2022)
Inflammation is a strong driver of atherosclerotic cardiovascular disease (ASCVD). There is a large unmet need for therapies that prevent or reduce excessive inflammation while avoiding systemic immunosuppression. We showed previously that selective inhibition of pro-inflammatory interleukin-6 (IL-6) trans-signalling by the fusion protein olamkicept (sgp130Fc) prevented and reduced experimental murine atherosclerosis in low-density lipoprotein receptor-deficient (Ldlr–/–) mice on a high-fat, high-cholesterol diet independently of low-density lipoprotein (LDL) cholesterol metabolism. Therefore, we allowed compassionate use of olamkicept (600 mg intravenously biweekly for 10 weeks) in a patient with very-high-risk ASCVD. Despite optimal LDL cholesterol under maximum tolerated lipid-lowering treatment, the patient had a remaining very high risk for future cardiovascular events related to significant arterial wall inflammation with lipoprotein (a) [Lp(a)]-cholesterol as the main contributor. 18Fluorodeoxyglucose positron emission tomography/computed tomography (18FDG PET/CT) measurements were performed before and after the treatment period. Olamkicept reduced arterial wall inflammation in this patient without interfering with lipoprotein metabolism. No clinical or laboratory side effects were observed during or after treatment with olamkicept. Our findings in this patient matched the results from our mechanistic study in Ldlr–/– mice, which were extended by additional analyses on vascular inflammation. Olamkicept may be a promising option for treating ASCVD independently of LDL cholesterol metabolism. A Phase II trial of olamkicept in ASCVD is currently being prepared.